2019
DOI: 10.1002/mgg3.1088
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2_e2 partially compensates for lack of MeCP2_e1: A male case of Rett syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: Rett syndrome (RTT) is a neurodevelopmental disorder that predominantly affects girls. Its causative gene is the X-linked MECP2 encoding the methyl-CpG-binding protein 2 (MeCP2). The gene comprises four exons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…The extent of overlap observed is, to a certain degree, unsurprising. It has been recently shown that MeCP2-E2 is able to partially compensate for the lack of the E1 isoform in a male case of RTT phenotype ( Takeguchi et al, 2020 ). However, the association of E1 with tubulin remains intriguing.…”
Section: Subsectionsmentioning
confidence: 99%
“…The extent of overlap observed is, to a certain degree, unsurprising. It has been recently shown that MeCP2-E2 is able to partially compensate for the lack of the E1 isoform in a male case of RTT phenotype ( Takeguchi et al, 2020 ). However, the association of E1 with tubulin remains intriguing.…”
Section: Subsectionsmentioning
confidence: 99%
“…Although several protein-coding and non-coding MECP2 transcripts have been identified or predicted ( Singh et al, 2008 ), the two most-studied splice variants of MeCP2 are known as MeCP2E1 and MeCP2E2 ( Kriaucionis and Bird, 2004 ; Mnatzakanian et al, 2004 ). Accordingly, MeCP2E1 and E2 isoform-specific expression, regulation, function, and clinical relevance to RTT have been the focus of several research studies ( Rastegar et al, 2009 ; Itoh et al, 2012 ; Kerr et al, 2012 ; Zachariah et al, 2012 ; Liyanage et al, 2013 , 2019 ; Olson et al, 2014 ; Yasui et al, 2014 ; Sheikh et al, 2017 ; Vogel Ciernia et al, 2018 ; Martinez de Paz et al, 2019 ; Takeguchi et al, 2020 ). Information about other MECP2 transcripts and their tissue- and cell-type specific expression could be obtained through RNA sequencing or data mining of related publically available data repositories.…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the first group have a mutation that causes classical RTT in females, though these boys have severe neonatal encephalopathy and a lifespan of less than one year and commonly die early during childhood. The diluting effect of X chromosome aneuploidy (Klinefelter syndrome; 47 XXY)) or somatic mosaicism may be associated with a milder phenotype, similar to atypical RTT [ 28 , 29 ]. The second group presents mutations which are different from typical/classical mutations in female patients but are more compatible with life into adulthood.…”
Section: Genetic Basis Of Rett Syndrome: Link Between Genotype Andmentioning
confidence: 99%